Tracing the Failure of Yemen’s Post – Arab Spring Democratic Transition: Sectarianization, Elite Fragmentation and Civil War - Maura Aprita Melinda; Adhi C. Fahadayna (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This article examines why Yemen’s post–Arab Spring democratic transition failed, asking how civil war reshaped political outcomes in a fragile democratization context. While existing studies often treat civil war as a consequence or background condition, this article advances the novel argument that armed conflict functioned as a decisive causal mechanism that transformed political incentives, eroded institutions, and displaced democratic competition with coercive power. Drawing on Democratic Peace Theory, the study argues that in systems marked by weak institutions and fragmented elite coalitions, incomplete democratization may intensify conflict rather than constrain it. Methodologically, the article employs a Comparative Historical Analysis that combines longitudinal data from the Varieties of Democracy (V-Dem) dataset (2010–2025) with qualitative evidence from policy reports and academic sources. Process tracing is used to reconstruct critical junctures, including the 2011 transition agreement, the failure of the National Dialogue Conference, and the 2014 Houthi takeover. Yemen is analyzed as a negative case in comparison with post–Arab Spring transitions that avoided civil war. The findings demonstrate that Yemen’s democratic failure was not driven solely by elite bargaining failures or sectarian polarization, but by civil war itself, which reconfigured elite strategies, accelerated institutional collapse, and produced path-dependent authoritarian outcomes